High-conductivity composite graphite negative electrode material and preparation method thereof
By combining graphite and silicon-based materials and forming composite graphite negative electrode materials through chemical vapor deposition method and coupling agent treatment, the problems of low conductivity and large volume changes in existing materials are solved, and high conductivity and excellent cycling stability are achieved.
Patent Information
- Application Number
- CN202411862255.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing graphite and silicon-based anode materials have problems such as low conductivity, poor capacity retention ability and excessive volume changes in lithium-ion batteries, which limit the performance of lithium-ion batteries.
By combining graphite and silicon-based materials, a composite graphite negative electrode material was prepared, and silicon was deposited by chemical vapor deposition method, treated with an amino group-containing silane coupling agent to form N-doped porous carbon coated on the silicon surface, while MXene nanosheets were coated on the surface of the porous carbon/silicon coated graphite product, and the oxidation resistance of MXene was improved by fluoro-containing silane coupling agent treatment.
It achieves high conductivity, excellent capacity and cycle stability, buffers the volume changes of graphite, porous carbon and silicon negative electrode materials during lithium embedding and deintercalation, and improves the overall performance of the battery.
Smart Images

Figure BDA0005193470850000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of graphite negative electrode materials, and in particular to a high-conductivity composite graphite negative electrode material and a preparation method thereof. Background Art
[0002] At present, carbon-based materials, silicon-based materials and other lithium-ion battery negative electrode materials are favored by experts. Carbon-based negative electrode materials such as graphite have the advantages of high electrical conductivity and easy embedding of lithium ions and are widely used in lithium-ion batteries. Graphite negative electrode materials usually include natural graphite and artificial graphite (asphalt, tar, etc.). However, the theoretical capacity of graphite is very small, and the formation of dendritic metallic lithium is inevitable when the graphite negative electrode is charged at a high rate, resulting in capacity decay. In addition, during the process of lithium ion extraction and embedding, carbon-based materials such as graphite negative electrode materials and porous carbon will also expand in volume, resulting in particle pulverization, which brings adverse factors to the battery's cycle performance.
[0003] Silicon-based materials, as negative electrode materials for lithium-ion batteries, have the advantages of large capacity, moderate operating potential, environmental friendliness, and high abundance, and have been widely used in lithium-ion batteries. However, due to the large volume change, poor capacity retention, and low inherent conductivity of silicon-based negative electrode materials during lithium insertion and deinsertion, pure silicon electrodes cannot meet the current requirements for the use of lithium-ion batteries.
[0004] Among two-dimensional (2D) materials, MXene is a new family of two-dimensional (2D) transition metal carbon / nitrides, which consists of M n+ 1AX n (n=1, 2, 3) by etching away the "A" layer, where M represents the early transition metal element, A represents the main group element, X represents carbon and / or nitrogen, and Tx represents the functional group connected to the M layer. x It is a typical representative of MXene, with a graphene-like structure, but T i3C2T x Has higher conductivity and Li than graphene + In addition, Ti3C2T x It also has the characteristics of low operating voltage, good hydrophilicity, rich surface functional groups, large specific surface area and interlayer spacing, and excellent mechanical properties. Thanks to these advantages, Ti3C2T x When applied to the negative electrode of lithium-ion batteries, it not only exhibits excellent physical and cycle stability, but also shows a huge pseudocapacitive contribution. x The theoretical capacity is low, and it is easy to self-stack during repeated charge and discharge. In addition, the edge of the MXene material may be adsorbed by oxygen and water molecules, which may cause Ti3C2T xPartial oxidation to non-conductive TiO2 limits the use of MXene materials in negative electrode materials.
[0005] Therefore, a suitable modification method is needed to combine graphite negative electrode materials and silicon-based negative electrode materials to obtain composite graphite negative electrode materials, so as to achieve complementary advantages and disadvantages in terms of conductivity and capacity, and then apply MXenes with improved oxidation resistance to composite graphite negative electrode materials. At the same time, it can make up for the defects of carbon-based materials such as graphite negative electrode materials and silicon-based negative electrode materials that have excessive volume changes during the extraction and embedding of lithium ions, so as to obtain composite graphite negative electrode materials with better comprehensive performance such as conductivity. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a high-conductivity composite graphite negative electrode material and a preparation method thereof.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A high conductivity composite graphite negative electrode material, the preparation of which comprises the following steps:
[0009] Step S1, placing graphite in a protective gas atmosphere, heating to 700-800°C, then introducing silane gas at a flow rate of 1-2L / min, and calcining at a constant temperature for 25-35min to obtain a silicon-coated graphite product; adding the silicon-coated graphite product to anhydrous ethanol, ultrasonically dispersing for 40-50min, then adding an amino-containing silane coupling agent, stirring and reacting at 60-70°C for 9-10h, and obtaining an NH2-silicon-coated graphite product;
[0010] Further, the protective gas is argon, and the protective gas flow rate is 1.5-2.0 L / min; the amount ratio of the silicon-coated graphite product, anhydrous ethanol, and the amino-containing silane coupling agent is 5-6 g: 100-120 mL: 10-11 g, and the amino-containing silane coupling agent is selected from one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane;
[0011] During the reaction of step S1, silicon is deposited on the graphite surface by chemical vapor deposition to obtain a silicon-coated graphite product; the silanol groups obtained by hydrolysis of the amino-containing silane coupling agent react with the active hydroxyl groups on the surface of the silicon-coated graphite product to form a NH2-silicon-coated graphite product;
[0012] Step S2, washing and drying the rice husk, and then putting it into an acid solution, heating it in a water bath at 80-85°C for 2-2.5h, washing it with water until it is neutral after cooling, and then drying it at 80-90°C, and then calcining it at 600-650°C in a protective gas atmosphere for 3-3.5h to obtain a carbon-containing composite; then adding the carbon-containing composite and potassium carbonate to a mortar and grinding them for 1-1.5h, and then calcining them at 900-950°C for 1-1.5h, washing them with water until they are neutral after cooling, filtering and drying them to obtain porous carbon; adding the porous carbon to a nitric acid solution, heating it at 90-100°C for 10-12h, cooling it to room temperature, washing it until it is neutral, and vacuum drying it at 80-90°C for 3-4h to obtain carboxylated porous carbon;
[0013] Furthermore, the ratio of rice husk to acid solution is 1-2g:50-60mL, and the acid solution is 2mol / L hydrochloric acid solution; the ratio of carbon-containing composite to potassium carbonate is 1-2g:3-6g; the ratio of porous carbon to nitric acid solution is 1g:40-50mL, and the mass fraction of nitric acid solution is 68-70%;
[0014] In the reaction process of step S2, alkali metal ions in the rice husk are removed by acid treatment; then, porous carbon is obtained by activation and pore formation by potassium carbonate at high temperature; and the porous carbon is acidified by nitric acid solution to obtain carboxylated porous carbon;
[0015] Step S3, adding the carboxylated porous carbon to DMF, adding dichlorothionyl under stirring, reflux stirring and reacting at 50-60° C. for 4-5 hours to obtain an acyl chloride product; stirring and mixing the NH2-silicon-coated graphite product, potassium carbonate and dimethyl sulfoxide to obtain a mixed solution 1, then adding the acyl chloride product to dimethyl sulfoxide and stirring and mixing to obtain a mixed solution 2, and dripping the mixed solution 2 into the mixed solution 1 under an ice-water bath, after the dripping is completed, heating to 45-50° C., stirring and reacting at a constant temperature for 12-14 hours, and distilling under reduced pressure to obtain a porous carbon / silicon-coated graphite product;
[0016] Further, the amount ratio of carboxylated porous carbon, DMF, and dichlorothionyl is 6-7g: 50-60mL: 4-5g; the amount ratio of NH2-silicon-coated graphite product, potassium carbonate, and dimethyl sulfoxide in mixed solution 1 is 7-8g: 1-1.5g: 55-65mL; the amount ratio of acyl chloride product and dimethyl sulfoxide in mixed solution 2 is 7-7.5g: 40-50mL; the amount ratio of mixed solution 1 and mixed solution 2 is 70-80mL: 50-60mL;
[0017] During the reaction of step S3, the carboxylated porous carbon reacts with thionyl chloride to obtain an acyl chloride product; the acyl chloride product reacts with the NH2-silicon-coated graphite product to coat the porous carbon on the surface of the silicon-coated graphite product to obtain a porous carbon / silicon-coated graphite product;
[0018] Step S4, adding Ti3AlC2 powder to the mixed solution, stirring at 35-40°C for 24-26h to obtain a suspension and washing with water until neutral, filtering and adding the precipitate to ethanol, ultrasonically dispersing in an ice water bath for 1-1.5h, adding the precipitate after centrifugation to deionized water, ultrasonically dispersing for 30-40min, and then centrifuging for 1-1.5h, collecting the supernatant to obtain a MXene nanosheet suspension;
[0019] Further, the Ti3AlC2 powder is 200-325 mesh, the mixed solution is obtained by mixing LiF and hydrochloric acid solution in a ratio of 2-2.5g:40-50mL, the amount ratio of Ti3AlC2 powder and mixed solution is 2-2.5g:45-55mL; the amount ratio of precipitate and ethanol is 2.8-3.0g:200-210mL, and the volume fraction of ethanol is 95%; the amount ratio of precipitate s and deionized water is 1.3-1.5g:150-160mL;
[0020] During the reaction of step S4, a suspension containing MXene nanosheets is prepared by chemical etching;
[0021] Step S5, adding the porous carbon / silicon-coated graphite product to ethanol and ultrasonically dispersing it for 30-40 minutes, then adding the MXene nanosheet suspension, stirring for 3-3.5 hours, vacuum filtering and vacuum drying at 60-70°C to obtain a MXene / porous carbon / silicon-coated graphite product; then adding the MXene / porous carbon / silicon-coated graphite product to ethanol and ultrasonically dispersing it for 1-1.5 hours, then adding a fluorine-containing silane coupling agent, stirring and reacting at 55-65°C for 18-20 hours, and then calcining at 500-600°C for 2-2.5 hours to obtain a high-conductivity composite graphite negative electrode material;
[0022] Furthermore, the amount ratio of the porous carbon / silicon coated graphite product, ethanol, and MXene nanosheet suspension is 0.1-0.2 g: 20-30 mL: 20-30 mL; the amount ratio of MXene / porous carbon / silicon coated graphite product, ethanol, and fluorine-containing silane coupling agent is 0.5-1.0 g: 100-110 mL: 13-15 g, and the fluorine-containing silane coupling agent is selected from one of tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, and heptadecafluorodecyltriisopropoxysilane; the volume fraction of ethanol is 95%;
[0023] During the reaction of step S5, the porous carbon / silicon-coated graphite product is hydrogen-bonded to the functional groups such as hydroxyl groups on the surface of the MXene nanosheets, and the MXene nanosheets are coated on the surface of the porous carbon / silicon-coated graphite product to obtain a MXene / porous carbon / silicon-coated graphite product; the MXene / porous carbon / silicon-coated graphite product is then reacted with the silicon hydroxyl groups obtained by hydrolysis of the fluorine-containing silane coupling agent to graft the fluorine-containing silane coupling agent onto the MXene, and then calcined to obtain a high-conductivity composite graphite negative electrode material.
[0024] Beneficial effects of the invention: The invention discloses a high-conductivity composite graphite negative electrode material and a preparation method thereof. The high-conductivity composite graphite negative electrode material is prepared by first depositing silicon on the graphite surface by chemical vapor deposition, and then treating with an amino-containing silane coupling agent to obtain an NH2-silicon-coated graphite product; then synthesizing porous carbon by the pore-forming effect of potassium carbonate, and treating the porous carbon with surface carboxylation to obtain carboxylated porous carbon; then the carboxylated porous carbon is reacted with the NH2-silicon-coated graphite product after chlorination, and the porous carbon is tightly coated on the surface of the silicon-coated graphite product to obtain a porous carbon / silicon-coated graphite product; then coating the MXene nanosheets prepared by chemical etching on the surface of the porous carbon / silicon-coated graphite product, and then treating with a fluorine-containing silane coupling agent to introduce fluorine into the MXene, and finally calcining to obtain the obtained product.
[0025] In the present invention, a graphite negative electrode material and a silicon-based negative electrode material are used together to obtain a composite graphite negative electrode material, which achieves complementary advantages and disadvantages in terms of conductivity and capacity; after carbonization, an amino-containing silane coupling agent forms N-doped porous carbon coated on the silicon surface, which can not only provide more electron and ion transport channels and pore spaces, but also avoid direct contact between silicon and electrolyte, thereby further improving the conductivity; since the oxidation of MXene usually starts from the edge, after being treated with a fluorine-containing silane coupling agent, the contact between the edge atoms of MXene and water molecules is cut off, thereby reducing the oxidation tendency and improving the oxidation resistance of MXene; MXene with high conductivity, excellent flexibility and improved oxidation resistance can further promote the transmission of electrons and ions, buffer the shortcomings of excessive volume changes of graphite negative electrode materials, porous carbon and silicon negative electrode materials during lithium insertion and deinsertion, so that the obtained high-conductivity composite graphite negative electrode material exhibits excellent conductivity, capacity and cycle stability. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] A high conductivity composite graphite negative electrode material, the preparation of which comprises the following steps:
[0029] Step S1, placing graphite (supplier: Shanghai Youmo Composite Materials Co., Ltd., product name: flake graphite) in an argon atmosphere with a gas flow rate of 1.5L / min, heating to 700°C, then introducing silane gas at a flow rate of 1L / min, and calcining at a constant temperature for 25min to obtain a silicon-coated graphite product; adding the silicon-coated graphite product to anhydrous ethanol, ultrasonically dispersing for 40min, and then adding 3-aminopropyltrimethoxysilane, stirring and reacting at 60°C for 9h to obtain NH2-silicon-coated graphite product; the amount ratio of silicon-coated graphite product, anhydrous ethanol, and 3-aminopropyltrimethoxysilane is 5g:100mL:10g;
[0030] Step S2, wash and dry the rice husk, put it into a 2 mol / L hydrochloric acid solution, heat it in a water bath at 80°C for 2h, wash it with water until it is neutral after cooling, dry it at 80°C, and then calcine it at 600°C in a nitrogen atmosphere for 3h to obtain a carbon-containing composite; then add the carbon-containing composite and potassium carbonate to a mortar and grind them for 1h, then calcine them at 900°C for 1h, wash them with water until they are neutral after cooling, filter and dry them to obtain porous carbon; add the porous carbon to a nitric acid solution with a mass fraction of 68%, heat it at 90°C for 10h, cool it to room temperature, wash it until it is neutral, and vacuum dry it at 80°C for 3h to obtain carboxylated porous carbon; the dosage ratio of rice husk to 2 mol / L hydrochloric acid solution is 1g:50mL; the dosage ratio of carbon-containing composite and potassium carbonate is 1g:3g; the dosage ratio of porous carbon to nitric acid solution with a mass fraction of 68% is 1g:40mL;
[0031] Step S3, adding the carboxylated porous carbon to DMF, adding dichlorothionyl under stirring, refluxing and stirring at 50°C for 4h to obtain an acyl chloride product; stirring and mixing the NH2-silicon-coated graphite product, potassium carbonate and dimethyl sulfoxide to obtain a mixed solution 1, and then adding the acyl chloride product to dimethyl sulfoxide and stirring and mixing to obtain a mixed solution 2, and dripping the mixed solution 2 into the mixed solution 1 under an ice-water bath, and after the dripping is completed, heating to 45°C, stirring and reacting at a constant temperature for 1 2h, vacuum distillation, that is, porous carbon / silicon-coated graphite product is obtained; the amount ratio of carboxylated porous carbon, DMF, and dichlorothionyl is 6g:50mL:4g; the amount ratio of NH2-silicon-coated graphite product, potassium carbonate and dimethyl sulfoxide in mixed solution 1 is 7g:1g:55mL; the amount ratio of acyl chloride product and dimethyl sulfoxide in mixed solution 2 is 7g:40mL; the amount ratio of mixed solution 1 and mixed solution 2 is 70mL:50mL;
[0032] Step S4, adding Ti3AlC2 powder to the mixed solution, stirring at 35°C for 24h to obtain a suspension and washing with water until neutral, filtering and adding the precipitate to ethanol, ultrasonically dispersing in an ice-water bath for 1h, centrifuging to obtain a precipitate s, adding it to deionized water, ultrasonically dispersing it for 30min, and then centrifuging it for 1h, collecting the supernatant to obtain a MXene nanosheet suspension; Ti3AlC2 powder is 200 mesh (supplier: Forsman Technology (Beijing) Co., Ltd., No.: 2203015), the mixed solution is obtained by mixing LiF and hydrochloric acid solution in a ratio of 2g:40mL, and the amount ratio of Ti3AlC2 powder to the mixed solution is 2g:45mL; the amount ratio of precipitate to ethanol is 2.8g:200mL, and the volume fraction of ethanol is 95%; the amount ratio of precipitate s to deionized water is 1.3g:150mL;
[0033] Step S5, adding the porous carbon / silicon-coated graphite product to ethanol and ultrasonically dispersing it for 30 minutes, then adding the MXene nanosheet suspension, stirring for 3 hours, vacuum filtering and vacuum drying at 60°C to obtain the MXene / porous carbon / silicon-coated graphite product; then adding the MXene / porous carbon / silicon-coated graphite product to ethanol and ultrasonically dispersing it for 1 hour, then adding tridecafluorooctyltrimethoxysilane, stirring and reacting at 55°C for 18 hours, and then calcining at 500°C for 2 hours to obtain a high conductivity composite graphite negative electrode material; the amount ratio of the porous carbon / silicon-coated graphite product, ethanol, and MXene nanosheet suspension is 0.1g:20mL:20mL; the amount ratio of the MXene / porous carbon / silicon-coated graphite product, ethanol, and tridecafluorooctyltrimethoxysilane is 0.5g:100mL:13g; the volume fraction of ethanol is 95%.
[0034] Example 2
[0035] A high conductivity composite graphite negative electrode material, the preparation of which comprises the following steps:
[0036] Step S1, placing graphite (supplier: Shanghai Youmo Composite Materials Co., Ltd., product name: flake graphite) in an argon atmosphere, heating to 700°C, then introducing silane gas at a flow rate of 1.5L / min, and calcining at a constant temperature for 30min to obtain a silicon-coated graphite product; adding the silicon-coated graphite product to anhydrous ethanol, ultrasonically dispersing for 45min, and then adding 3-aminopropyltriethoxysilane, stirring and reacting at 65°C for 9.5h to obtain NH2-silicon-coated graphite product; the protective gas is argon, and the protective gas flow rate is 1.5L / min; the amount ratio of the silicon-coated graphite product, anhydrous ethanol, and 3-aminopropyltriethoxysilane is 5.5g:110mL:10.5g;
[0037] Step S2: Wash and dry the rice husks and place them in a l / L hydrochloric acid solution, heated in a water bath at 82℃ for 2.2h, washed with water to neutrality after cooling, then dried at 85℃, and then calcined at 620℃ in a nitrogen atmosphere for 3.2h to obtain a carbon-containing composite; then the carbon-containing composite and potassium carbonate were added to a mortar and ground for 1.3h, and then calcined at 920℃ for 1.2h, washed with water to neutrality after cooling, filtered and dried to obtain porous carbon; the porous carbon was added to a nitric acid solution with a mass fraction of 69%, heated at 95℃ for 11h, cooled to room temperature, washed to neutrality, and vacuum dried at 85℃ for 3.5h to obtain carboxylated porous carbon; the dosage ratio of rice husk to 2mol / L hydrochloric acid solution was 1.5g:55mL; the dosage ratio of carbon-containing composite and potassium carbonate was 1.5g:4.5g; the dosage ratio of porous carbon to nitric acid solution with a mass fraction of 69% was 1g:45mL;
[0038] Step S3, adding the carboxylated porous carbon to DMF, adding thionyl chloride under stirring, reflux stirring and reacting at 55°C for 4.5h to obtain an acyl chloride product; stirring and mixing the NH2-silicon-coated graphite product, potassium carbonate and dimethyl sulfoxide to obtain a mixed solution 1, then adding the acyl chloride product to dimethyl sulfoxide and stirring and mixing to obtain a mixed solution 2, and dripping the mixed solution 2 into the mixed solution 1 under an ice-water bath, and after the dripping is completed, heating to 47°C, stirring and reacting at a constant temperature for 13h, reducing The porous carbon / silicon-coated graphite product was obtained by pressure distillation; the amount ratio of carboxylated porous carbon, DMF, and dichlorothionyl was 6.5g:55mL:4.5g; the amount ratio of NH2-silicon-coated graphite product, potassium carbonate, and dimethyl sulfoxide in mixed solution 1 was 7.5g:1.2g:60mL; the amount ratio of acyl chloride product and dimethyl sulfoxide in mixed solution 2 was 7.2g:45mL; the amount ratio of mixed solution 1 to mixed solution 2 was 75mL:55mL;
[0039] Step S4, adding Ti3AlC2 powder to the mixed solution, stirring at 37°C for 25h to obtain a suspension and washing with water until neutral, filtering and adding the precipitate to ethanol, ultrasonically dispersing in an ice-water bath for 1.2h, centrifuging to obtain a precipitate s, adding it to deionized water, ultrasonically dispersing it for 35min, and then centrifuging it for 1.2h, collecting the supernatant to obtain a MXene nanosheet suspension; Ti3AlC2 powder is 200 mesh (supplier: Forsman Technology (Beijing) Co., Ltd., No.: 2203009), the mixed solution is obtained by mixing Li F and hydrochloric acid solution in a ratio of 2.2g:45mL, and the amount ratio of Ti3AlC2 powder to the mixed solution is 2.2g:50mL; the amount ratio of precipitate to ethanol is 2.9g:205mL, and the volume fraction of ethanol is 95%; the amount ratio of precipitate s to deionized water is 1.4g:155mL;
[0040] Step S5, adding the porous carbon / silicon-coated graphite product to ethanol and ultrasonically dispersing it for 35 minutes, then adding the MXene nanosheet suspension, stirring for 3.2 hours, vacuum filtering and vacuum drying at 65°C to obtain the MXene / porous carbon / silicon-coated graphite product; then adding the MXene / porous carbon / silicon-coated graphite product to ethanol and ultrasonically dispersing it for 1.2 hours, then adding tridecafluorooctyltriethoxysilane, stirring and reacting at 60°C for 19 hours, and then calcining at 550°C for 2.3 hours to obtain a high conductivity composite graphite negative electrode material; the amount ratio of the porous carbon / silicon-coated graphite product, ethanol, and MXene nanosheet suspension is 0.15g:25mL:25mL; the amount ratio of the MXene / porous carbon / silicon-coated graphite product, ethanol, and tridecafluorooctyltriethoxysilane is 0.7g:105mL:14g; the volume fraction of ethanol is 95%.
[0041] Example 3
[0042] A high conductivity composite graphite negative electrode material, the preparation of which comprises the following steps:
[0043] Step S1, placing graphite (supplier: Shanghai Youmo Composite Materials Co., Ltd., product name: flake graphite) in an argon atmosphere, heating to 800°C, then introducing silane gas at a flow rate of 2L / min, and calcining at a constant temperature for 35min to obtain a silicon-coated graphite product; adding the silicon-coated graphite product to anhydrous ethanol, ultrasonically dispersing for 50min, and then adding N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, stirring and reacting at 70°C for 10h to obtain NH2-silicon-coated graphite product; the protective gas is argon, and the protective gas flow rate is 2.0L / min; the amount ratio of the silicon-coated graphite product, anhydrous ethanol, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 6g:120mL:11g;
[0044] Step S2, wash and dry the rice husk, put it into a 2mol / L hydrochloric acid solution, heat it in a water bath at 85°C for 2.5h, wash it with water until it is neutral after cooling, dry it at 90°C, and then calcine it at 650°C in a nitrogen atmosphere for 3.5h to obtain a carbon-containing composite; then add the carbon-containing composite and potassium carbonate to a mortar and grind it for 1.5h, then calcine it at 950°C for 1.5h, wash it with water until it is neutral after cooling, filter it and dry it to obtain porous carbon; add the porous carbon to a nitric acid solution with a mass fraction of 70%, heat it at 100°C for 12h, cool it to room temperature, wash it until it is neutral, and vacuum dry it at 90°C for 4h to obtain carboxylated porous carbon; rice husk, 2mol / L hydrochloric acid solution, heat it at 100°C for 12h, cool it to room temperature, wash it until it is neutral, and vacuum dry it at 90°C for 4h to obtain carboxylated porous carbon; The usage ratio of l / L hydrochloric acid solution is 2g:60mL; the usage ratio of carbon-containing composite and potassium carbonate is 2g:6g; the usage ratio of porous carbon and 70% nitric acid solution is 1g:50mL;
[0045] Step S3, adding the carboxylated porous carbon to DMF, adding dichlorothionyl under stirring, refluxing and stirring at 60°C for 5h to obtain an acyl chloride product; stirring and mixing the NH2-silicon-coated graphite product, potassium carbonate and dimethyl sulfoxide to obtain a mixed solution 1, and then adding the acyl chloride product to dimethyl sulfoxide and stirring and mixing to obtain a mixed solution 2, and dripping the mixed solution 2 into the mixed solution 1 under an ice-water bath, and after the dripping is completed, heating to 50°C, stirring and reacting at a constant temperature for 14h , vacuum distillation, that is, porous carbon / silicon-coated graphite product is obtained; the amount ratio of carboxylated porous carbon, DMF, and dichlorothionyl is 7g:60mL:5g; the amount ratio of NH2-silicon-coated graphite product, potassium carbonate and dimethyl sulfoxide in mixed solution 1 is 8g:1.5g:65mL; the amount ratio of acyl chloride product and dimethyl sulfoxide in mixed solution 2 is 7.5g:50mL; the amount ratio of mixed solution 1 and mixed solution 2 is 80mL:60mL;
[0046] Step S4, adding Ti3AlC2 powder to the mixed solution, stirring at 40°C for 26h to obtain a suspension and washing with water until neutral, filtering and adding the precipitate to ethanol, ultrasonically dispersing in an ice-water bath for 1.5h, centrifuging to obtain a precipitate s, adding it to deionized water, ultrasonically dispersing it for 40min, and then centrifuging it for 1.5h, collecting the supernatant to obtain a MXene nanosheet suspension; Ti3AlC2 powder is 325 mesh (supplier: Forsman Technology (Beijing) Co., Ltd., No.: 2203026), the mixed solution is Li F and hydrochloric acid solution mixed in a ratio of 2.5g:50mL, the amount ratio of Ti3AlC2 powder to the mixed solution is 2.5g:55mL; the amount ratio of precipitate to ethanol is 3.0g:210mL, and the volume fraction of ethanol is 95%; the amount ratio of precipitate s to deionized water is 1.5g:160mL;
[0047] Step S5, adding the porous carbon / silicon-coated graphite product to ethanol and ultrasonically dispersing it for 40 minutes, then adding the MXene nanosheet suspension, stirring for 3.5 hours, vacuum filtering and vacuum drying at 70°C to obtain the MXene / porous carbon / silicon-coated graphite product; then adding the MXene / porous carbon / silicon-coated graphite product to ethanol and ultrasonically dispersing it for 1.5 hours, then adding heptadecafluorodecyltriisopropoxysilane, stirring and reacting at 65°C for 20 hours, and then calcining at 600°C for 2.5 hours to obtain a high conductivity composite graphite negative electrode material; the amount ratio of the porous carbon / silicon-coated graphite product, ethanol, and the MXene nanosheet suspension is 0.2g:30mL:30mL; the amount ratio of the MXene / porous carbon / silicon-coated graphite product, ethanol, and heptadecafluorodecyltriisopropoxysilane is 1.0g:110mL:15g; the volume fraction of ethanol is 95%.
[0048] Comparative Example 1
[0049] Compared with Example 3, the high conductivity composite graphite negative electrode material is replaced with Compound 1, which is obtained by calcining the porous carbon / silicon-coated graphite product in Step S3 at 600°C for 2.5h, that is, no MXene is introduced, and no fluorine-containing silane coupling agent is used for treatment. The rest is exactly the same as Example 3.
[0050] Comparative Example 2
[0051] Compared with Example 3, the high conductivity composite graphite negative electrode material is replaced with Compound 2, which is obtained by calcining the MXene / porous carbon / silicon-coated graphite product in step S5 at 600°C for 2.5h, that is, no fluorine-containing silane coupling agent is used for treatment, and fluorine is not introduced into the MXene. The rest is exactly the same as Example 3.
[0052] The high conductivity composite graphite negative electrode material prepared by the present invention is further tested for its effect, and the test results are as follows.
[0053] The high conductivity composite graphite negative electrode material obtained in Example 1-3 and Comparative Example 1-2 was used as the negative electrode material of lithium ion battery, lithium iron phosphate was used as the positive electrode material, LiPF6 / EC+DEC (the volume ratio of EC to DEC was 1:1) was used as the electrolyte, and a glass fiber membrane was used as the separator, and a 5AH soft pack battery was prepared accordingly. The performance of the prepared battery was tested with reference to the method in GB / T24533-2009 "Graphite negative electrode materials for lithium ion batteries"; at the same time, the composite graphite negative electrode material was immersed in deionized water and allowed to stand for 6 hours, and the conductivity after oxidation was tested with reference to the above method; the obtained results were recorded in Table 1;
[0054] Table 1: Test results
[0055]
[0056] According to the data in Table 1, the high conductivity composite graphite negative electrode material of the present invention has excellent conductivity, capacity and cycle stability. As can be seen from Example 3 compared with Comparative Example 1, without the introduction of MXene and without the treatment of fluorine-containing silane coupling agent, the transmission of electrons and ions cannot be further promoted, and the volume change of the buffered graphite negative electrode material, porous carbon and silicon negative electrode material during the lithium insertion and deinsertion process is too large. The conductivity, capacity and cycle stability of the composite graphite negative electrode material are all reduced. As can be seen from Example 3 compared with Comparative Example 2, without the treatment of fluorine-containing silane coupling agent, that is, without the introduction of fluorine to MXene, the oxidation resistance of MXene is not improved, the conductivity of the composite graphite negative electrode material after oxidation decreases, the capacity retention rate after 600 cycles also decreases, and the cycle stability decreases.
[0057] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A high conductivity composite graphite negative electrode material, characterized in that: The steps include: Step S1, placing graphite in a protective gas atmosphere, introducing silane gas after heating, and calcining at a constant temperature to obtain a silicon-coated graphite product; adding the silicon-coated graphite product to anhydrous ethanol, and treating it with an amino-containing silane coupling agent to obtain an NH2-silicon-coated graphite product; Step S2, washing and drying the rice husk, placing it in an acid solution, heating and drying it, and then calcining it in a protective gas atmosphere to obtain a carbon-containing composite; grinding the carbon-containing composite and potassium carbonate, calcining them, and treating them to obtain porous carbon; adding the porous carbon to a nitric acid solution and heating it for reaction to obtain a carboxylated porous carbon; Step S3, adding the carboxylated porous carbon to DMF and reacting with dichlorothionyl to obtain an acyl chloride product; stirring and mixing the NH2-silicon-coated graphite product, potassium carbonate and dimethyl sulfoxide to obtain a mixed solution 1; then adding the acyl chloride product to dimethyl sulfoxide and stirring and mixing to obtain a mixed solution 2; under an ice-water bath, dropping the mixed solution 2 into the mixed solution 1, stirring and reacting to obtain a porous carbon / silicon-coated graphite product; Step S4, adding Ti3AlC2 powder to the mixed solution, stirring to obtain a suspension, washing with water until neutral, filtering and adding the precipitate to ethanol, ultrasonically dispersing and centrifuging to obtain a precipitate s, adding it to deionized water, ultrasonically dispersing and centrifuging again, and then collecting the supernatant to obtain a MXene nanosheet suspension; Step S5, adding the porous carbon / silicon-coated graphite product to ethanol and stirring the MXene nanosheet suspension to obtain a MXene / porous carbon / silicon-coated graphite product; then adding the MXene / porous carbon / silicon-coated graphite product to ethanol for ultrasonic dispersion, treating it with a fluorine-containing silane coupling agent and calcining it to obtain a high-conductivity composite graphite negative electrode material.
2. A high conductivity composite graphite negative electrode material according to claim 1, characterized in that: In step S1, the protective gas is argon, the protective gas flow rate is 1.5-2.0L / min, and the silane gas flow rate is 1-2L / min; the amount ratio of the silicon-coated graphite product, anhydrous ethanol, and the amino-containing silane coupling agent is 5-6g:100-120mL:10-11g, and the amino-containing silane coupling agent is selected from 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
3. The high conductivity composite graphite negative electrode material according to claim 1, characterized in that: In step S2, the ratio of rice husk to acid solution is 1-2g:50-60mL, and the acid solution is 2mol / L hydrochloric acid solution; the ratio of carbon-containing complex to potassium carbonate is 1-2g:3-6g; the ratio of porous carbon to nitric acid solution is 1g:40-50mL, and the mass fraction of nitric acid solution is 68-70%.
4. The high conductivity composite graphite negative electrode material according to claim 1, characterized in that: In step S3, the usage ratio of carboxylated porous carbon, DMF, and dichlorothionyl is 6-7 g: 50-60 mL: 4-5 g; the usage ratio of NH2-silicon-coated graphite product, potassium carbonate, and dimethyl sulfoxide in the mixed solution 1 is 7-8 g: 1-1.5 g: 55-65 mL.
5. The high conductivity composite graphite negative electrode material according to claim 1, characterized in that: In step S3, the usage ratio of the acyl chloride product and dimethyl sulfoxide in the mixed solution 2 is 7-7.5 g:40-50 mL; the usage ratio of the mixed solution 1 and the mixed solution 2 is 70-80 mL:50-60 mL.
6. The high conductivity composite graphite negative electrode material according to claim 1, characterized in that: In step S4, the Ti3AlC2 powder is 200-325 mesh, the mixed solution is obtained by mixing LiF and hydrochloric acid solution in a ratio of 2-2.5g:40-50mL, and the amount ratio of Ti3AlC2 powder to mixed solution is 2-2.5g:45-55mL.
7. The high conductivity composite graphite negative electrode material according to claim 1, characterized in that: In step S4, the usage ratio of the precipitate to ethanol is 2.8-3.0 g: 200-210 mL, and the volume fraction of ethanol is 95%; the usage ratio of the precipitate to deionized water is 1.3-1.5 g: 150-160 mL.
8. The high conductivity composite graphite negative electrode material according to claim 1, characterized in that: In step S5, the usage ratio of the porous carbon / silicon-coated graphite product, ethanol, and MXene nanosheet suspension is 0.1-0.2 g: 20-30 mL: 20-30 mL.
9. The high conductivity composite graphite negative electrode material according to claim 1, characterized in that: In step S5, the amount ratio of MXene / porous carbon / silicon-coated graphite product, ethanol, and fluorine-containing silane coupling agent is 0.5-1.0 g: 100-110 mL: 13-15 g, and the fluorine-containing silane coupling agent is selected from one of tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane and heptadecafluorodecyltriisopropoxysilane; the volume fraction of ethanol is 95%.
10. A high-conductivity composite graphite negative electrode material prepared by the method for preparing a high-conductivity composite graphite negative electrode material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of expanded graphite / silicon@carbon negative electrode material for lithium ion batteries
CN106356519A
Negative electrode active material, electrochemical device, and electronic device
CN115836408A
Silicon-carbon composite negative electrode material and preparation method and application thereof
CN117878273A
Winding drum driving device for stage equipment
KR102322985B1